2012
DOI: 10.1055/s-0032-1308704
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Readability and Quality of Web Pages Addressing both Common and Uncommon Topics in Pediatric Surgery

Abstract: Websites devoted to pediatric surgical topics have higher readability and quality information for disease diagnosis and natural history. Otherwise, the quality of pediatric surgical information on the Internet is high for CT and UT. A high reading level is required to use these resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
2
7
1
Order By: Relevance
“…This is in accordance to former studies on benign diseases [17-19]. A study on Spanish web pages on PCa showed that 31% of cancer web pages displayed quality seals, 62% provided adequate references, and 54% offered information on the last update [12].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in accordance to former studies on benign diseases [17-19]. A study on Spanish web pages on PCa showed that 31% of cancer web pages displayed quality seals, 62% provided adequate references, and 54% offered information on the last update [12].…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, tools like ­DISCERN shall help to evaluate the quality of information provided online [14]. So far, the quality of information on the web has been investigated for different benign conditions [17-19]. …”
Section: Introductionmentioning
confidence: 99%
“…General search engines are by far the most popular means for locating medical information but are often not oriented to providing accurate information for the layperson. A good hospital website makes recommendation easier . There are guidelines detailing how a website should be structured to help with ease of reading and navigation .…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult for parents and patients to find a reliable source of health information on the internet. The majority of health websites do not provide equity of access to paediatric surgical information as they require a high English reading level . This is especially relevant given that many paediatric patients also access the internet for health information.…”
Section: Introductionmentioning
confidence: 99%
“…The quality sources of different algorithms, equations, and formulas used for programming of clinical calculators are available [16,17]. However, criteria of reliability of Internet-based healthcare information are less known and standardized [18,19]. The Google Scholar-driven search is used as a primary source of knowledge, despite controversies in opinions about reliability [20,21].…”
Section: Discussionmentioning
confidence: 99%